Kajian Terhadap Kecenderungan Keusahawanan dalam Kalangan Pelajar Jurusan Perdagangan SMK Seksyen 24(C)Shah Alam Selangor - Hasniza, Hafidzin (2011)
The purpose of this study is to identify the entrepreneurial intentions among commerce students of SMK Seksyen 24(2) Shah Alam Selangor. Besides that, the other purpose of this study to identify student profile, the level of entrepreneurial intentions, to identify the level of interest in entrepreneurial careers and the relationship between entrepreneurial intentions with his interest in entrepreneurial careers. The instrument used to measure dependent and independent variables was developed based on previous study. The independent variable is the demography factor and entrepreneurial intentions and dependent variable is the interest in entrepreneurial careers. 91 questionnaires were distributed among commerce students of SMK Seksyen 24(2) Shah Alam Selangor and 91 questionnaires were returned back to the researcher and the data gathered was analyzed using the Statistical Package for Social Science (SPSS),17th version .The analysis showed the significant difference on level of entrepreneurial intentions and level of interest in entrepreneurial careers. Based on these findings, critical personality factors such as proactive personality and innovative should be instilled so as arouse students’ interest on business and therefore, helps to create employment opportunities.